Visibility Interrupted : Rural Queer Life and the Politics of Unbecoming - Thomsen, Carly Ann (Book collections on Project MUSE., 2021)
"A questioning of the belief in the power of LGBTQ visibility through the lives of queer women in the rural Midwest"--